Prevalence and pattern of adverse events following immunization to Covishield vaccine in a tertiary care hospital: a cross-sectional analytical study - Sumedhan, Suji V.; Gopinath, Sangeetha; Gopan, Karthika (International Journal Of Community Medicine And Public Health, 2023)
Background: The COVID-19 pandemic has emerged as the most important public health issue in the past two years. Multiple preventive and treatment modalities are being tried to contain this pandemic. Several countries have documented vaccines as a vital tool to combat this pandemic across the globe. Hence, we tried to evaluate the adverse events following immunisation at the study site following Covishield vaccination among front-line health workers in our tertiary care hospital. Methods: A cross-sectional descriptive study was planned in the vaccination site of our institute, where all details of the frontline workers who were vaccinated for the Covishield vaccine were included, and they were followed up to study the prevalence and pattern of AEFIs. The participants were observed for 30 minutes after the jab and were reviewed/called upon on the third day following immunization to gather information. The data was collected using a semi-structured questionnaire Results: Our study included around 159 frontline workers and medical students who received their vaccination during the study period. The mean age distribution was 24.3±7.6 years, with female predominance. We observed an AEFI prevalence of 33.3% among the study participants at the end of 30 minutes, while after 30 mins and during the next 3 days of follow-up by our staff, we observed that the prevalence increased to 80%. We observed that the commonest AEFI observed at 30 minutes and during the 3 days follow up was tenderness/pain, fever, body ache and light-headedness. Only 4% of the patients required hospitalisation following AEFI. Conclusions: Around 1/3rd of our study participants reported AEFI following vaccination during the first 30 minutes of observation which is much higher than the national average.